Exploring Online Reviews in Indonesia: Impacts on UGC Platforms and Consumers - Muhammad Nidhal; Sharfina Indrayadi; Louis Budiman; Aang Sutrisna (Center for Indonesian Policy Studies (CIPS), 2024)
The rapid development of technology and the digital economy has enabled every individual as a consumer to share their opinions with other users through reviews. Online reviews, as an integral part of the digital economy, are among the key factors that influence consumer behavior and purchase decisions. While the proliferation of online review practices can benefit both businesses and consumers, challenges remain in terms of the quality and reliability of the reviews, complexity of content moderation, and data privacy and protection issues. In the online review ecosystem, consumers - as the reviewers, and platforms - as the review system providers - are the primary actors, each playing important roles. In its practice, Law No. 8/1999 on Consumer Protection protects the rights and governs the obligations of consumers as reviewers. Meanwhile, user-generated content (UGC) platforms are responsible for evaluating and responding to the review contents, as regulated under the Minister of Communications and Informatics (MOCI) Regulation No. 5/2020 on Electronic System Organizers (ESOs) in the Private Sector. The interactions between them also imply new rights and obligations related to data protection in accordance with Law No. 27/2022 on Personal Data Protection (PDP Law), which necessitates attention from all involved parties.
Keywords: 330